In-situ stress evaluation of coal measures based on logging parameters-A case study of Xishanyao formation in the Southern margin of Junggar basin - Shuai Yang; Xinxin Fang; Yunhong Wang; Fengling Li (Scientific Reports, 2025)
Abstract Based on acoustic and density logging data, the in-situ stress calculation model is established. The in-situ stress of Xishanyao coal measure strata in the southern margin of Junggar Basin is evaluated by integrating the improved differential strain analysis of principal direction, wave velocity anisotropy and paleomagnetic method. The results indicated that: (1) The error between the principal stress predicted by the in-situ stress model based on logging parameters and the measured value was less than 8%, which met the needs of the accuracy of application; (2) The maximum horizontal principal stress direction was near northwest direction, 56.6°~82.0° and the distribution trend of horizontal principal stress is small in two wings, but large in the middle; (3) When the coefficient of horizontal stress difference is smaller than 0.3, complexed fracture network could be formed with hydraulic fracturing, otherwise the network was relatively simple; (4) The stress type in the studied area belongs to Type III, namely $$\:{{\upsigma\:}}_{\text{H}}>{{\upsigma\:}}_{\text{V}}>{{\upsigma\:}}_{\text{h}}$$ , which has a good protective effect on the opening and conductivity of natural fractures, in addition conducive to the vertical tensile fracture produced by hydraulic fracturing. The lateral expansion ability of pressure fractures produced in this procedure is strong.